PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA PESERTA DIDIK KELAS XII IPA SMA N 1 LEMBAH GUMANTI - Safitri, Niza Destria (Departemen Matematika, 2024)
The goal of mathematics education is to improve problem solving skills. The cooperative learning method used is TSTS. This study tested whether students who learn Two Stay Two Stray type cooperative learning can solve math problems better than students who learn directly. The quasi-experimental method used was Non-equivalent Posttest Only Control Group Design. This study involved XII science students of SMA N 1 Lembah Gumanti in the 2023/2024 school year. The experimental and control groups, XII IPA 4 and 2, were selected using Simple Random Sampling. The P-value of the math problem solving test was 0.007 below α of 0.05 indicating the rejection of the null hypothesis (H0). Students who learn TSTS cooperative solve math problems better than students who learn directly.Keywords– Mathematical Problem Solving Ability, Two Stay Two Stray Cooperative Learning Model